Who likes jargon? The joint effect of jargon type and industry knowledge on investors’ judgments - Tan, Hun-Tong (2020)
We experimentally investigate how jargon affects investment willingness for investors with different industry knowledge, and whether such effects vary with good or bad jargon. We find that for investors without industry knowledge, jargon decreases investment willingness because it decreases understanding. However, for investors with some but low industry knowledge, jargon increases investment willingness because it increases perceived product premium. Such effects exist whether good or bad jargon is used. Finally, investors with high industry knowledge differentiate between good and bad jargon, and reduce investment willingness only when bad jargon is used. These findings have implications for regulators, managers, and investors.